KITAB KUNING, IJTIHAD POLITIK, DAN KONTEKS NEGARA-BANGSA: KONSTRUKSI FIKIH SIYĀSAH PESANTREN - Muhammad Adib; Roihanah (Jurnal Penelitian Ilmiah INTAJ, 2022)
This study aims to reveal the construction of pesantren’s fiqh of politics, namely the dialectical movement between two opposite dimensions. The first dimension is the kitab kuning which is static and was born between the 8th century and the early 20th century. The second dimension is the pesantren's political ijtihad which is dynamic and progressive, but still refers to the kitab kuning. With a philosophical and historical approach, this study shows that the driving axis of the dialectic between the static kitab kuning and the dynamic and progressive pesantren’s political ijtihad is the epistemic system (‘aql) which binds the cognitive awareness of pesantren and is passed down from generation to generation from the early days to the present. Its manifestation is cognitive flexibility in the form of an eclectic trend in choosing literature and scholars’ opinions and the manhajī method of thinking behind the qaulī method used. With this cognitive flexibility, pesantren interpret the kitab kuning based on the the nation-state context and produce various dynamic and progressive products of political ijtihad.